A Critical Study on Vicharchika and Its Comparative Management with Durvadi Lepa and Abhayaristadi Churna w.s.r. to Eczema - Sahu, Narayan; Mohanta, Sarita; Panda, P K; Nayak, Utkalini (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: The skin is one of the largest organs and mirror image of the body, constitutes 16% of the human body weight. It weighs around 5 kg and covers an area of about 2 square meters. It covers the whole surface of the body. As per the symptometology, Vicharchika has been directly correlated with eczema (dermatitis) in modern science, which is defined as a non-contagious inflammation, due to low grade infection of skin characterized by erythema, scaling, edema, vasiculation, and oozing. In today’s medical practice, there is no suitable therapy. Only local use of steroids produces symptomatic relief. Shodhan and Shaman are the main therapy options for Vicharchika in Ayurveda. Durvadi lepa and Abhayaristadi churna are the formulations mentioned in Bhaisajya ratnavali indicated for the management of Kustha. Aims and Objectives: The aim of the study was to study about the comparative clinical efficacy of Durvadi lepa and Abhayaristadi churna in the management of Vicharchika. Materials and Methods: This is a single-blind comparative clinical study with a pre-test and post-test design. The patients were randomly categorized into two groups. Thirty patients of Group A (15) and Group B (15) patients were registered from outpatient department and inpatient department of Government Ayurvedic College and Hospital, Balangir, presented with subjective parameters and objective parameters. After diagnosis, they were under trial with Ayurvedic formulations of Durvadi Lepa given 10 g once daily at evening time for local application and Abhayaristadi Churna given 3–6 g twice daily after food with luke warm water for a period of 30 days, respectively. The subjective and objective parameters were assessed in 10-day interval to interpret the result by statistical evaluation. Observation and Results: It had been observed that the result of trial drug Group A patients was significant (0.05) to reduce both subjective and objective parameters after 30 days of treatment as compared to Group B patients. In GroupA, 93.33% of patients had marked improvement, while 6.67% of patients had moderate improvement and 0.00% mildly improved. In Group B, 66.67% of patients had marked improvement and 20.00% moderate and 13.33% mildly improved. In both groups, the result was statistically significant, but improvement was noticed more in Group A. Conclusion: On comparison between two groups, Durvadi lepa had shown more effect than Abhayaristadi churna. No adverse effects were noticed during clinical trial in both groups.